A New Rule for Setting the Margin for the Basic Rate of Charge. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
In April 2008, the Executive Board adopted a package of measures to reform the Fund's income model. This followed an intensive work program building on the recommendations of an independent committee appointed by the Managing Director to study options for sustainable long-term financing for the Fund. The resulting new income model aims to broaden the Fund's income sources and reduce its reliance on lending income as the primary source of revenue. This new model includes: (i) creating an endowment funded with the profits from a limited sale of the Fund's gold holdings; (ii) expanding the Fund's investment authority to enhance the expected return on the Fund's investments; and (iii) resuming the practice of reimbursing the General Resources Account (GRA) for the cost of administering the PRG Trust.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States